(3LhGH GHf JjejI Yf eTgO GdMSjfs - (3GdfejQj GdMQGfj GdOeTbqj GdMfHdj, CHh GdYHGS, GHf nJrjpenqjI, Jbj GdOjf, CMeO Hf YHO GdMdje Hf YHO GdSdGe, (B728 (3g`s ((3GdeDdas)
(3ChdgG (B:s
(3HSe Gddg (B.. (3eG Jbhd GdSGOI GdYdeGA CFeI GdOjf hgOGI GdeSdejf QVj Gddg Yfge CLeYjf (B.. (3aj GdeTgO GdefShH Edi GdMSjf QVj Gddg Yfg HeOjfI GdYGeQI gd gh UMjM Ce dG (B...s
(3BNQgG (B:s
... (3hHgPG GdESfGO YHO Gddg Hf gGTe KfG YHO GdQMef Hf (B... (3Yf MSf Hf MGRe hCjhH bGdG cGf YeQ Hf YHO GdYRjR jYLHg Cf JWdb GdJj de JMV YfO GdgdGd (B... (3hGdMeO ddgs
(3YdjgG ebGHdI ZjQ hGVMIs
(3JHUQI GdYfhGf (B:s
(3GNJda YfhGf GdcJGH ceG gh eYQha Yf eUfaGJ TjN GdESdGes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdGYdGe (B1\144s
(3GdGYdGe (B1\144s
Keywords: (3GdJGQjNs